Influence of wall number and surface functionalization of carbon nanotubes on their antioxidant behavior in high density polyethylene - Shi, Xiaomei; Jiang, Binbo; Wang, Jingdai; Yang, Yongrong (Carbon (New York), 2012)
Carbon nanotubes (CNTs) are extensively incorporated as reinforcement into polymeric materials due to their extraordinary properties. The antioxidant ability of CNTs in high density polyethylene (HDPE) was studied. Single-walled carbon nanotubes (SWCNTs), multi-walled carbon nanotubes (MWCNTs), and hydroxylated multi-walled carbon nanotubes (MWCNTs-OH) were involved to investigate the influence of wall number and surface functionalization of CNTs on their antioxidant behavior in HDPE. Based on measurements of the oxidation induction temperature and oxidation induction time of CNT/HDPE composites, it is found that the antioxidant ability of the three kinds of CNTs is in the following order: MWCNTs-OH > MWCNTs > SWCNTs. The antioxidant ability and mechanism of CNTs are further examined by electron spin resonance spectra and Raman spectra. It is observed that the antioxidant behavior of CNTs obeys a free radical scavenging mechanism. The order of the radical scavenging efficiency and the defect concentration for CNTs are in good agreement with that of their antioxidant ability in HDPE. With more walls and surface hydroxyl groups, the CNTs have more structural defects and exhibit higher antioxidant ability. The study raises the possibility that CNTs can improve antioxidant properties as well as mechanical properties of polymer matrix.